Etnomatematika Budaya Ende pada Konsep Bilangan Bulat sebagai Dasar Penyusunan Lembar Kerja Peserta Didik - Maria Apriliana Nona Musi; Yosefina A.N. Noning; Teofilus Putra Wete Ratu; Wahida Muhammad (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2026)
This study aims to identify the concept of integers contained in three cultural elements of the Ende community, namely the Tu Ngawu traditional ceremony (antar belis), the Gawi traditional dance, and Ende ikat weaving, and to use them as the basis for compiling local wisdom-based Student Worksheets (LKPD). The research was motivated by students' low understanding of the concept of integers, especially operations on negative numbers, as well as the limited teaching materials that integrate local Ende culture. The study used a qualitative approach with an exploratory research type. Data were obtained through in-depth interviews with two informants and documentation, then analyzed descriptively-interpretively. The results show that Tu Ngawu contains the concept of positive and negative integers, and the balance of debt and receivables; the Gawi dance represents integers through forward-backward movements; while Ende ikat weaving contains the concept of integers in thread counting, motif patterns, and numbering of motif positions. Based on these findings, a local wisdom-based LKPD was compiled as a contextual integer learning medium for students in Ende Regency.